6, 7‐Benzotropolone Syntheses Based on Ring‐Closing Metatheses and Four‐Electron Oxidations. Issue 19 (12th May 2020) - Kreibich, Michael; Gemander, Manuel; Peter, David; Yadav, Dharmendra B.; de Koning, Charles B.; Fernandes, Manuel A.; Green, Ivan R.; van Otterlo, Willem A. L.; Brückner, Reinhard
Abstract : Four homoallyl ortho ‐vinylaryl ketones (10a ‐d ) – 1, 8‐dienes of sorts – were prepared by several approaches. In the presence of 1–2 mol‐% Grubbs‐II catalyst, they ring‐closed to give 6, 7‐dihydrobenzocyclohepten‐5‐ones (11a ‐d ) in 90–96 % yield. With SeO2 the parent compound (11a ) delivered benzocyclohepten‐5‐one (13a ) and/or selenium‐containing compounds (18 –22 ) but no more than traces of 6, 7‐benzotropolone (5a ). However, 5a was accessible from compound 11a via the sodium enolate and allowing it to react with a stream of oxygen (43 % yield). The sodium enolates of the substituted 6, 7‐dihydrobenzocyclohepten‐5‐ones 11b–d and oxygen underwent analogous 4‐electron oxidations. This furnished the substituted 6, 7‐benzotropolones 11b ‐d . In contrast, the corresponding lithium enolates were inert towards oxygen. The 6, 7‐dihydrobenzocyclohepten‐5‐one 11d was also accessed differently, namely by a Grubbs‐II catalyst‐mediated RCM/C=C migration tandem reaction of the allyl ortho ‐allylaryl ketone 73 – another 1, 8‐diene of sorts (90 % yield). Abstract : Homoallyl ortho ‐vinylaryl ketones were prepared through several different routes. In the presence of 1–2 mol‐% Grubbs‐II catalyst, these substrates cyclized to give 6, 7‐dihydrobenzocyclohepten‐5‐ones. The enolates derived therefrom by treatment with NaHMDS in THF were oxidized by a stream of molecular oxygen at 0 °C. This furnished 6‐hydroxybenzocyclohepten‐5‐ones ("6, 7‐benzotropolones").